The EU refugee crisis: The tip of a global iceberg - Maystadt, Jean-François; Breisinger, Clemens (International Food Policy Research Institute, 2015)
The current refugee movements undoubtedly constitute a huge challenge, yet existing evidence suggests that economic impacts are likely to be small in rich countries. Likewise in the developing countries that host refugees, impacts can be positive if sufficient external assistance is provided. The global community has a moral obligation to assist refugees. Richer countries should not only accept refugees for resettlement within their own borders, but also shoulder much of the financial burden for poorer host countries in order to assure positive and peaceful outcomes for both refugees and their host countries.